-(9x+1)-7=-8x-(x+8)

Simple and best practice solution for -(9x+1)-7=-8x-(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(9x+1)-7=-8x-(x+8) equation:



-(9x+1)-7=-8x-(x+8)
We move all terms to the left:
-(9x+1)-7-(-8x-(x+8))=0
We get rid of parentheses
-9x-(-8x-(x+8))-1-7=0
We calculate terms in parentheses: -(-8x-(x+8)), so:
-8x-(x+8)
We get rid of parentheses
-8x-x-8
We add all the numbers together, and all the variables
-9x-8
Back to the equation:
-(-9x-8)
We add all the numbers together, and all the variables
-9x-(-9x-8)-8=0
We get rid of parentheses
-9x+9x+8-8=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| -28=-14b | | x=(0.75)(24)24=0.25x | | x=(0.75)(24) | | x=(0.25)(24) | | -3^2+15x=18 | | 30=2(x×-1) | | x=(0.8)(15) | | 200=10j | | 2(f+13)=30 | | 0.25/1=j | | ×+2y=-1,-×+2y=25 | | 62.5=5s | | 3x-4=3(x-1)+12 | | 7+.20p=5+.30p= | | 4x-7=41-4x | | 6^x+2=4^3x-4 | | x-16=23;7 | | k/6+9=5 | | 50200000x2984=935000xx | | X–(4x2)=12 | | 6(x-5)+22=6x-7 | | 4(l+5)+-9=23 | | 14.88+x=17.07 | | s/2+1=9 | | 5(x-7)+32=5x-3 | | |3x+5|-7=0 | | -4(-32+-8y)=-64 | | (5*2-8x+5)+(8*2+x-9)=0 | | (5*2-8x+15)+(8*2+x-9)=0 | | -5(2x-17)=2(x-3)-5 | | -2e-6=-18 | | 6h^2-6h-1=0 |

Equations solver categories